Design of wireless web-based multiplatform system for thermal environmental control of broiler facilities using fuzzy set theory - COSME TEIXEIRA DA SILVA; TADAYUKI YANAGI JUNIOR; RAPHAEL WINCKLER DE BETTIO; MARCELO BAHUTI (Anais da Academia Brasileira de Ciências)
Abstract The control and monitoring process for broiler facilities needs to be improved to mitigate or eliminate birds’ thermal stress. Thus, the objective was to develop of a fuzzy controller embedded in a microcontroller and a multiplatform web application that communicates with the fuzzy controller to control the aviary climate system. An architecture based on the Internet of Things (IoT) and agribusiness 4.0 was used to implement a fuzzy controller embedded in a microcontroller. Data were collected by temperature and humidity sensors. A multiplatform web application communicated the climate system to the fuzzy controller. This information was transmitted to the central web server via message queuing telemetry transport (MQTT). The system performed decision-making to control the aviary thermal environment of broilers ranging from one to 49 days old. The input variables of the system were the black globe-humidity index (BGHI) and the bird age. Defuzzification by the center of gravity method produced environmental ratings that were used to control the thermal environment automatically and smartly. Using the intelligent prototype produced a 98% accuracy in the validation process. This low-cost system can be used as an agribusiness 4.0 application to mitigate thermal stress conditions in aviaries and, consequently, reduce productivity losses.